For the Defence of the British Empire: Edwin Montagu and the Turkish Peace Settlement in a Transnational Context - PAPUÇÇULAR, HAZAL (My University, 2020)
This article aims to analyse the position of Edwin Montagu, the renowned British politician and the Secretary of State for India between 1917 and 1922, towards the Turkish peace settlement in the post-war period. Montagu supported the fair treatment of Turkey by the Allies, reflecting a deep discrepancy within the British policy making given the stern anti-Turkish positions of the Prime Minister Lloyd George and the Foreign Office headed by George Curzon. This study suggests that Montagu’s ideas regarding Turkey were shaped by the necessities that his job entailed – to keep the British Raj intact – as millions of Muslims living in India were highly interested in the future of the Caliphate and organized under the banner of Khilafat Movement. Thus, this article emphasizes that the attitude of Montagu was closely related to the defence of the British Empire although the British interests were formulated differently by the different organs of the state. In this respect, the Secretary’s political duty to serve the national interests in an anxious international and transnational setting made him pro-Turkish in a compulsory way, leading to his eventual forced resignation in 1922.
Keywords: Edwin Montagu; The Treaty of Sevres; Transnationalism; Turkish War of Independence